Drawings from the border - Francesco Piobbichi (Freedom from Fear, 2018)
If I had not lived in Lampedusa, I would have never found the inner resilience to narrate these stories of migration through drawings. Moreover, at the age of 40-something, I would have never depicted the emotions making me able to describe these last four years spent on working along this European-Mediterranean border.